The Role of Public Health Center Staffs in Socialization, Education and Campaign to Increase Exclusive Breastfeeding Coverage - Syahputri, Rezyana Budi; Akmal, Dzul (JHE (Journal of Health Education), 2020)
Background: The achievement of breastfeeding in Surakarta City in 2017 was 76.7% while the target of infants with exclusive breastfeeding is 80%. The lowest achievement of exclusive breastfeeding was at Gilingan Public Health Center (66.1%). The role of health center staff is very important in improving and supporting social breastfeeding efforts. Methods: The study was descriptive qualitative research using a case study approach. The informant of this research consists of 2 main informants and 3 triangulation informants with a purposive sampling technique. Results: The role of health center staff in socialization were in the form of counseling and individual counseling; education program were in the form of class for pregnant women and class for parents with under-five children. There has been no health campaign implementation in the World Breastfeeding Week celebration. Conclusions: The socialization and education program could be implemented but for the campaign has not been implemented. It was because of a lack of coordination by Gilingan Public Health Center’s staff.